2007
DOI: 10.1007/s10482-007-9208-9
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriocin-like inhibitory substances from Campylobacter spp.

Abstract: Twenty-five Campylobacter isolates were screened for production of antimicrobial substances using a deferred antagonism assay. Sixteen isolates showed activity against either Staphylococcus aureus, Salmonella enterica serovar Enteritidis or Candida albicans. The inhibitory activity was sensitive to treatment with pronase E, trypsin and pepsin, suggesting that the antimicrobial compound(s) are proteinaceous. Activity spectra of isolates included S. aureus, Micrococcus luteus, Streptococcus sp., Bacillus subtili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 5 publications
1
2
0
Order By: Relevance
“…Other studies showed an inhibitory effect of P. intermedia , isolated from the subgingival plaque of HIV-infected patients, on the formation of C. albicans germ tubes ( Nair et al., 2001 ). A similar effect was also observed for another bacterium from the group of bridging colonizers— Campylobacter —that through the secretion of bacteriocin-like substances with antimicrobial activity inhibited the growth of C. albicans laboratory strain ATCC 44859 as detected using measurements of the zone of inhibition ( Workman et al., 2007 ).…”
Section: Albicans Ability To Form a Multispecies Biofilm Community In Periodontal Diseasessupporting
confidence: 57%
“…Other studies showed an inhibitory effect of P. intermedia , isolated from the subgingival plaque of HIV-infected patients, on the formation of C. albicans germ tubes ( Nair et al., 2001 ). A similar effect was also observed for another bacterium from the group of bridging colonizers— Campylobacter —that through the secretion of bacteriocin-like substances with antimicrobial activity inhibited the growth of C. albicans laboratory strain ATCC 44859 as detected using measurements of the zone of inhibition ( Workman et al., 2007 ).…”
Section: Albicans Ability To Form a Multispecies Biofilm Community In Periodontal Diseasessupporting
confidence: 57%
“…This correlation is in agreement with the findings of Navazesh et al [69], who showed that antiretroviral therapy increased the risk for recovering bacteria (including Campylobacter species) with a concomitant decrease in the recovery rate of Candida , in HIV-infected women. Moreover, Workman et al [70] reported that proteins secreted by Campylobacter inhibit the growth of C. albicans . The clinical relevance of this correlation remains to be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…It is supposed that many bacteria belonging to Proteobacteria including Escherichia coli and Pseudomonas aeruginosa are antagonistic to C. albicans. [67][68][69] In fact, the presence of Enterobacteriaceae is essential for the modulation of colitis with overgrown C. albicans. 70 Furthermore, there are also several other microbiota which might play non-negligible roles in colitis progress in this study, such as Campilobacterota, Actinobacteriota and Deferribacterota.…”
Section: Food and Functionmentioning
confidence: 99%